You are a badass at making money: master the mindset of wealth - Sincero, Jen (London John Murray, 2018)
From the author of You Are A Badass, the New Your Times bestselling book everyone is talking about.YOU ARE A BADASS AT MAKING MONEY is the book you need if you've spent too much time watching money land in your bank account and then roll through your fingers. Jen Sincero went from living in a converted garage to traveling the world in 5-star luxury in a matter of years, and knows all too well the layers of BS one can get wrapped up in around money, as well as what it takes to dig your way out. In this funny, fascinating and practical book she goes in-depth on how powerful our thoughts are and how our bank accounts are mirrors for our beliefs about money. YOU ARE A BADASS AT MAKING MONEY combines laugh out loud comedy with life-changing concepts, all boiled down into manageable, bite-sized tips so that YOU can put them into practice and get life changing results.
Keywords: Collection of stories on wealth